Pathogenic bacterial profile, associated factors, and antimicrobial susceptibility patterns in intra-city public transport in Harar City, Eastern Ethiopia - Sultan, Nejib; Seyoum, Ayichew; Ayele, Firayad; Mekonnnen, Getachew Kabew (Frontiers in Public Health, 2025)
BackgroundPublic transportation plays a vital role in urban settings, especially with the expansion of mass transit systems. However, concerns have arisen regarding the spread of antibiotic-resistant bacterial pathogens, primarily through contact with surfaces in public transport. There is limited data on this topic in Eastern Ethiopia, particularly in Harar. Therefore, this study aimed to assess the pathogenic bacterial profile, antimicrobial susceptibility patterns, and associated factors in intra-city public transport in Harar City, Eastern Ethiopia, from 20 June to 30 October 2023.MethodsA cross-sectional study was conducted involving 258 intra-city public transport vehicles selected through convenience sampling. The data collection process was conducted using structured questionnaires administered to drivers, and swab samples were obtained from frequently touched surfaces, such as seats, handles, and doors. These specimens were shipped to a laboratory within 2 h for microbiological analysis. Statistical analysis was performed using SPSS version 21. Linear and logistic regression analyses were employed to identify factors associated with pathogenic bacteria contamination, with statistical significance established at a p-value of <0.05 and a 95% confidence interval (CI).ResultsA total of 258 vehicles were sampled, with pathogenic bacteria isolated from 192 vehicles, resulting in an isolation rate of 74.4% (95% CI: 69–80%). The mean colony-forming unit (CFU) count was 2.994 × 104 (SD: ± 0.562 × 104 CFU). The predominant pathogens identified included coagulase-negative Staphylococci (40.3%), Staphylococcus aureus (27.5%), Klebsiella species (11.6%), and Escherichia coli (10.9%). High antimicrobial resistance rates were observed, particularly against ampicillin (97.6%) and oxacillin (56.5%) in Gram-positive isolates, while Gram-negative rods exhibited varied resistance patterns. Multidrug resistance was detected in 22.5% of isolates. Significant factors associated with pathogenic bacteria contamination included sampling location (handles and seats), multiple routes, high passenger counts, unclean surfaces, and afternoon sampling.ConclusionThis study highlights alarming levels of bacterial contamination in public transport, the prevalence of pathogenic bacteria, and significant antibiotic resistance. Implementing effective hygiene measures and ensuring regular sanitation are essential to mitigating microbial risks and controlling the spread of community-acquired infections.